Schibsby v Westenholz and the recognition and enforcement of judgments in England - Dickinson, A (Sweet and Maxwell, 2018)
Challenges claims that the 1870 ruling in Schibsby v Westenholz (QB) is a great decision regarding recognition and enforcement of foreign judgments in England. Reviews the facts of Schibsby and its long-term influence on establishing a closed approach to the authority of foreign courts. Critically examines the court's reasoning, suggests how the approach it introduced is flawed, and proposes an alternative policy drawn from earlier case law.